MENINGKATKAN KESADARAN DALAM BERWIRAUSAHA MELALUI POTENSI HASIL PANEN (MIE TOMAT) - Andhika Giri Persada (UII, 2015)
The majority of people in Indonesia live in the village. Not a few people of Indonesia who came from the village leaving the village to find a decent job in the city.This thought is certainly one, but a deserted village has the potent ial to move forward.Crops and livestock in abundance will be very profitable if managed correctly. For thewelfare of rural communities, it takes training that is to grow the ability of ruralcommunities. Creativity and innovation in managing crops and livestock to be of higheconomic value is needed. One way for the welfare of rural communities is to provideentrepreneurial training and explanation. Entrepreneurship is a process of doingsomething creative and new or different (innovative) are useful in providing more value. Gejayan hamlet located in Pakis subdistrict, Magelang is a hamlet whose majorityare farmers. Yields are the largest of Hamlet Gejayan tomatoes. Because tomatoes areabundant harvest, the price of tomatoes to be very low. Many farmers are losing money due to the gains a bit. It takes innovation in managing tomatoes are abundant. Tomatonoodles are noodles that uses the basic ingredients of tomatoes. In the field of healthnoodles consumed tomatoes better than the noodles instant noodles are sold inIndonesia. Tomato noodle products were also given the attractive packaging to attractconsumers. With the tomato noodle products, is expected to improve the localeconomy Gejayan Hamlet.